Extending knowledge management beyond organisational borders – barriers for South African construction organisations - Osborne, Jeremy (Department of Construction Economics and Management, 2021)
Previous research raised the question of why South African organisations do not extend their Knowledge Management (KM) practices beyond their organisational borders. Therefore, there is a need to examine the barriers faced by construction organisations when trying to extend KM activities beyond organisational borders towards encouraging the South African construction sector to improve upon its collective KM maturity. This research utilised a quantitative approach which initially examined the available literature on the topic of Knowledge Management and the barriers found inhibiting its implementation. From this knowledge a survey instrument was developed and circulated to 499 construction professionals based in South Africa to elicit their opinions on Knowledge Management, extending KM activities beyond organisational boundaries and the barriers potentially inhibiting these activities. A total of 93 usable data sets were received and subjected to statistical analysis. This research found that there was a clear positive opinion towards KM and to extending these activities beyond organisational borders. The perception that by extending KM activities beyond organisational borders may negatively impact the organisations competitiveness is still prevalent and is a barrier to extending KM activities beyond organisational borders. Further it was found that the lack of time allocated to KM activities was an inhibitor to KM activities bother internally and from extending these KM activities beyond organisational borders. However, the amount of training given on KM and support of management was only found to be of significant concern in the less mature organisations and therefore may inhibit KM activities but were not a clear inhibitor to extending these activities beyond organisational borders. Continuity in the makeup of project teams was identified as a potential route to improve project performance and the current contracts utilised in the sector did not appear to currently impact knowledge sharing. Encouragingly it was found that knowledge was not withheld by employees to improve job security and further the challenges faced by multiple languages being spoken in the project environment and in coordinating TMO's did not register as significant inhibitors to knowledge sharing. This research's findings show that professionals in the South African construction sector have a positive opinion towards KM and extending these activities beyond organisational borders. Barriers do exist in the sector that are inhibiting knowledge managements implementation and growth, however by highlighting these issues it is possible for organisations to overcome the challenges faced, grow their knowledge management maturity and extract the most out of the strategies implemented. Based on these findings, the study recommended that there is a need to establish partnerships and longstanding relationships which foster knowledge transfer to overcome the negative perception that extending knowledge management activities beyond organisational borders may negatively impact competitiveness. This research was limited by the response rate to the survey circulated being low with only 93 valid data sets in the sample for statistical analysis. Further most respondents to the survey were from small and micro organisations who had low KM maturities and therefore the results for this research cannot claim to represent the construction sector of South Africa as a whole.